Non-aqueous electrolyte storage element
Patent Information
- Application Number
- JP2023143157
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-14
AI Technical Summary
【0008】 本発明の一側面に係る非水電解質蓄電素子は、負極における継続的な不可逆容量の発生の低減効果が高い。
Smart Images

Figure 2025035850000002 
Figure 2025035850000003 
Figure 2025035850000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-aqueous electrolyte electricity storage element. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion non-aqueous electrolyte secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally include an electrode assembly having a pair of electrodes electrically isolated by a separator, and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring charge-transporting ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries.
[0003] For the purpose of increasing the energy density of such nonaqueous electrolyte storage elements and improving the charge / discharge efficiency, carbon materials such as graphite are used as the negative electrode active material of the nonaqueous electrolyte storage elements (see Patent Document 1). Also, in order to form a protective film on the negative electrode, an additive is generally added to the electrolyte. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2005-222933 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, depending on the combination of the negative electrode active material and the additive in the electrolyte, continuous irreversible capacity may occur in the nonaqueous electrolyte storage element, resulting in a decrease in capacity.
[0006] An object of the present invention is to provide a nonaqueous electrolyte electricity storage element which is highly effective in reducing the occurrence of continuous irreversible capacity in the negative electrode. [Means for solving the problem]
[0007] A nonaqueous electrolyte storage element according to one aspect of the present invention includes a negative electrode including a negative electrode active material, a positive electrode including a positive electrode active material, and a nonaqueous electrolyte including an imide salt, and the negative electrode active material has a BET specific surface area of 6.0 m 2 / g or less, and the imide salt is lithium (difluorophosphonyl)fluorosulfonylimide, lithium bis(fluorosulfonyl)imide, lithium bis(difluorophosphonyl)imide, or a combination thereof. Effect of the Invention
[0008] The nonaqueous electrolyte electricity storage element according to one aspect of the present invention is highly effective in reducing the occurrence of continuous irreversible capacity in the negative electrode. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a perspective view showing one embodiment of a nonaqueous electrolyte electricity storage element. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] First, an overview of the nonaqueous electrolyte electricity storage element disclosed in this specification will be described.
[0011] (1) A nonaqueous electrolyte storage element according to one embodiment of the present invention includes a negative electrode including a negative electrode active material, a positive electrode including a positive electrode active material, and a nonaqueous electrolyte including an imide salt, and the negative electrode active material has a BET specific surface area of 6.0 m 2 / g or less, and the imide salt is lithium (difluorophosphonyl)fluorosulfonylimide, lithium bis(fluorosulfonyl)imide, lithium bis(difluorophosphonyl)imide, or a combination thereof.
[0012] According to the nonaqueous electrolyte storage element described above in (1), the BET specific surface area of the negative electrode active material is 6.0 m 2 / g or less, and the non-aqueous electrolyte contains an imide salt such as lithium (difluorophosphonyl)fluorosulfonylimide, lithium bis(fluorosulfonyl)imide, lithium bis(difluorophosphonyl)imide, or a combination thereof, which effectively reduces the occurrence of continuous irreversible capacity in the negative electrode. The reason for this is unclear, but is thought to be as follows. The non-aqueous electrolyte storage element described in (1) above has a BET specific surface area of 6.0 m 2 By using a negative electrode active material with a molecular weight of 0.1 to 1.0 μm / g or less, the reductive decomposition of the imide salt in the negative electrode is suppressed. This allows the imide salt to act mainly on the positive electrode, and as a result, the oxidative decomposition of the non-aqueous electrolyte in the positive electrode can be suppressed. The compound generated by the oxidative decomposition of the non-aqueous electrolyte has high activity, and when this compound moves through the non-aqueous electrolyte and reaches the negative electrode, it undergoes reductive decomposition while involving the surrounding non-aqueous electrolyte. Therefore, it is presumed that the non-aqueous electrolyte storage element described in (1) above has a high effect of reducing the generation of continuous irreversible capacity in the negative electrode, since the compound generated by oxidative decomposition is less likely to be generated. Here, the "BET specific surface area" is determined by a nitrogen adsorption method in which the pressure and the amount of adsorption are measured based on the physical adsorption of nitrogen molecules to the particle surface by immersing the sample in liquid nitrogen and supplying nitrogen gas. As a specific measurement method, the nitrogen adsorption amount (m 2 The amount of nitrogen adsorption thus obtained is divided by the mass (g) of the sample to obtain the BET specific surface area (m 2 / g).
[0013] (2) In the nonaqueous electrolyte storage element described above in (1), the content of the imide salt in the nonaqueous electrolyte may be 0.5% by mass or more and 2.0% by mass or less.
[0014] According to the nonaqueous electrolyte storage element described in (2) above, by setting the content of the imide salt within the above range, the effect of suppressing the reductive decomposition of the imide salt in the negative electrode can be improved. In particular, by setting the content of the imide salt to 2.0 mass% or less, the reductive decomposition of the imide salt present in excess can be prevented. Therefore, the generation of continuous irreversible capacity in the negative electrode of the nonaqueous electrolyte storage element described in (2) above can be more effectively reduced.
[0015] (3) In the nonaqueous electrolyte storage element according to (1) or (2), the potential of the positive electrode active material at the end-of-charge voltage during normal use is 3.9 V (vs. Li / Li + ) or more.
[0016] According to the nonaqueous electrolyte storage element described above in (3), the potential at the end of charge during normal use is 3.9 V (vs. Li / Li + ) or more, the energy density of the nonaqueous electrolyte storage element can be improved. The higher the potential of the positive electrode active material at the end-of-charge voltage, the more significant the oxidative decomposition of the nonaqueous electrolyte. Therefore, the positive electrode protection effect of the imide salt is more effectively exerted. "During normal use" refers to a case where the nonaqueous electrolyte storage element is used under charge / discharge conditions recommended or specified for the nonaqueous electrolyte storage element.
[0017] The configuration of a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention, the configuration of an electricity storage device, and a method for manufacturing a nonaqueous electrolyte electricity storage element, as well as other embodiments, will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.
[0018] <Configuration of Nonaqueous Electrolyte Energy Storage Element> A nonaqueous electrolyte storage element (hereinafter, also simply referred to as "storage element") according to one embodiment of the present invention includes an electrode assembly having a negative electrode, a positive electrode, and a separator, a nonaqueous electrolyte, and a container that contains the electrode assembly and the nonaqueous electrolyte. The electrode assembly is usually of a laminated type in which a plurality of negative electrodes and a plurality of positive electrodes are stacked with a separator interposed therebetween, or of a wound type in which a negative electrode and a positive electrode are stacked with a separator interposed therebetween and wound. The nonaqueous electrolyte exists in a state in which it is impregnated in the negative electrode, the positive electrode, and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as "secondary battery") will be described.
[0019] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer.
[0020] The negative electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity is 10 or less, as measured in accordance with JIS-H-0505 (1970). -2 The threshold value is Ω·cm. Metals such as copper, nickel, stainless steel, and nickel-plated steel, or alloys thereof, and carbonaceous materials are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foil, vapor deposition film, mesh, and porous materials, and foil is preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.
[0021] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.
[0022] The intermediate layer is a layer disposed between the negative electrode substrate and the negative electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the negative electrode substrate and the negative electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.
[0023] The negative electrode active material layer contains a negative electrode active material and, if necessary, any optional components such as a conductive agent, a binder, a thickener, and a filler.
[0024] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.
[0025] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li 4 Ti 5 O 12 , LiTiO 2、 TiNb 2 O 7 Examples of the material include titanium-containing oxides such as titanium oxide, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite and non-graphitic carbon are preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.
[0026] "Graphite" means a material that has an average lattice spacing (d 002) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. From the viewpoint of excellent input / output characteristics, natural graphite is preferred.
[0027] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.
[0028] Here, the "discharged state" of a carbon material such as graphite means a state in which the carbon material, which is a negative electrode active material, is discharged so that charge transport ions such as lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material, which is a negative electrode active material. For example, in a half cell using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and lithium metal (Li) as a counter electrode, the open circuit voltage is 0.7 V or more.
[0029] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.
[0030] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.
[0031] The upper limit of the BET specific surface area of the negative electrode active material is 6.0 m 2 / g or less, 5.5m 2 / g is preferable. When the BET specific surface area of the negative electrode active material is equal to or less than the upper limit, reductive decomposition of the imide salt in the negative electrode is suppressed. This allows the imide salt to act mainly in the positive electrode, and as a result, continuous oxidative decomposition of the non-aqueous electrolyte in the positive electrode can be suppressed. The lower limit of the BET specific surface area of the negative electrode active material is 4.0 m 2When the BET specific surface area of the negative electrode active material is equal to or greater than the lower limit, it is possible to obtain favorable efficient discharge characteristics while obtaining the effects of the present invention.
[0032] In the present specification, the BET specific surface area of the negative electrode active material is measured by the following method. The nitrogen adsorption amount (m 2 The amount of adsorption thus obtained is divided by the mass (g) of the sample to obtain the BET specific surface area (m 2 / g). For the measurement, gas adsorption is performed by cooling using liquid nitrogen. In addition, before cooling, preheating is performed at 120°C for 15 minutes. The amount of the measurement sample is 0.5g ± 0.1g.
[0033] The negative electrode active material is usually a particle (powder). In order to obtain a powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. Examples of the pulverizing method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. When pulverizing, wet pulverization in which water or a non-aqueous solvent such as hexane is present can also be used. As a classification method, a sieve, a wind classifier, or the like is used as necessary for both dry and wet methods. When the negative electrode active material is a metal such as metallic Li, the negative electrode active material may be in the form of a foil.
[0034] The average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbon material such as graphite, a titanium-containing oxide, or a polyphosphate compound, the average particle size may be 1 μm or more and 100 μm or less. When the negative electrode active material is Si, Sn, Si oxide, Sn oxide, or the like, the average particle size may be 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the production or handling of the negative electrode active material becomes easy. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the negative electrode active material layer is improved.
[0035] "Average particle size" refers to the value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%, based on the particle size distribution measured by laser diffraction / scattering method in accordance with JIS-Z-8825 (2013) for a solution obtained by diluting particles with a solvent.
[0036] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 90% by mass to 98% by mass. By setting the content of the negative electrode active material in the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.
[0037] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. The graphite, graphitizable carbon, and non-graphitizable carbon also have electrical conductivity, but the graphite, graphitizable carbon, and non-graphitizable carbon are not included in the conductive agent in the negative electrode active material layer. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitizable carbon, graphene-based carbon, and the like. Examples of non-graphitizable carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, and ketjen black. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), and fullerene. Examples of the shape of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in a composite form. For example, a composite material of carbon black and CNT may be used. Of these, carbon black is preferred from the viewpoints of electronic conductivity and coatability, and acetylene black is particularly preferred.
[0038] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0039] The content of the binder in the negative electrode active material layer is preferably from 0.5% by mass to 5% by mass, and more preferably from 0.8% by mass to 3% by mass.
[0040] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.
[0041] The content of the thickener in the negative electrode active material layer is, for example, preferably from 0.1% by mass to 6% by mass, and more preferably from 0.5% by mass to 3% by mass.
[0042] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof.
[0043] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the negative electrode above.
[0044] The positive electrode substrate has electrical conductivity. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or alloys thereof are used. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high electrical conductivity, and cost. Examples of the positive electrode substrate include foil, vapor deposition film, mesh, and porous material, and foil is preferred from the viewpoint of cost. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).
[0045] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.
[0046] The positive electrode active material layer includes a positive electrode active material. The positive electrode active material layer includes optional components such as a conductive agent, a binder, a thickener, and a filler, as necessary. The optional components such as a conductive agent, a binder, a thickener, and a filler can be selected from the materials exemplified for the negative electrode above.
[0047] The positive electrode active material can be appropriately selected from known positive electrode active materials. As the positive electrode active material for a lithium ion secondary battery, a material capable of absorbing and releasing lithium ions is usually used. As the positive electrode active material, for example, α-NaFeO 2 Lithium transition metal composite oxides having a crystalline structure, lithium transition metal composite oxides having a spinel crystalline structure, polyanion compounds, chalcogen compounds, sulfur, etc.2 As an example of a lithium transition metal composite oxide having a crystalline structure, Li[Li x Ni (1-x) ]O 2 (0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O 2 (0≦x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co (1-x) ]O 2 (0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O 2 (0≦x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O 2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O 2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β). Lithium transition metal composite oxides with spinel crystal structure include Li x Mn 2 O 4 , Li x Ni γ Mn (2-γ) O 4 Examples of polyanion compounds include LiFePO 4 , LiMnPO 4 , LiNiPO 4 , LiCoPO 4 , Li 3 V 2 (PO 4 ) 3 , Li 2 MnSiO 4 , Li 2 CoPO 4Examples of the chalcogen compound include titanium disulfide, molybdenum disulfide, and molybdenum dioxide. The atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.
[0048] The potential of the positive electrode active material at the end of charge during normal use is 3.9V (vs. Li / Li + ) or higher, and 4.1V (vs. Li / Li + By using a positive electrode active material whose potential at the end-of-charge voltage during normal use is equal to or higher than the above lower limit, the energy density of the nonaqueous electrolyte storage element can be improved.
[0049] As a positive electrode active material having a potential at the end of charge voltage during normal use that is equal to or higher than the lower limit, for example, in the case of a lithium transition metal composite oxide, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 , LiNi 3 / 5 Co 1 / 5 Mn 1 / 5 O 2 , LiNi 1 / 2 Co 1 / 5 Mn 3 / 10 O 2 , LiNi 1 / 2 Co 3 / 10 Mn 1 / 5 O 2 , LiNi 8 / 10 Co 1 / 10 Mn 1 / 10 O 2 Among these lithium transition metal composite oxides, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 is preferred.
[0050] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. When a composite of the positive electrode active material and another material is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. The pulverizing method and the classifying method can be selected, for example, from the methods exemplified for the negative electrode.
[0051] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.
[0052] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0053] (Non-aqueous electrolyte) The non-aqueous electrolyte includes an imide salt, a non-aqueous solvent, and an electrolyte salt dissolved in the non-aqueous solvent.
[0054] The type and content of salt contained in the non-aqueous electrolyte are identified by ion chromatography (IC). Water is used as the eluent. Specifically, the procedure is as follows. A series of measurements is performed continuously under the same conditions. (1) Collection of non-aqueous electrolyte First, the nonaqueous electrolyte storage element is disassembled to remove the nonaqueous electrolyte. If the nonaqueous electrolyte cannot be removed, the nonaqueous electrolyte storage element is centrifuged to remove the nonaqueous electrolyte. If the nonaqueous electrolyte cannot be removed even after centrifugation, an appropriate extraction solvent (e.g., acetonitrile) is injected into the nonaqueous electrolyte storage element, and the nonaqueous electrolyte diluted with the extraction solvent is removed. (2)IC analysis The components of the collected non-aqueous electrolyte are analyzed by IC. The IC analysis is performed in the following order: qualitative analysis and quantitative analysis. (qualitative analysis) A measurement sample (non-aqueous electrolyte) is subjected to IC analysis. The components contained in the measurement sample are predicted from the peak positions of each peak in the obtained ion chromatogram. A known sample of the predicted components (hereinafter referred to as "predicted components") is subjected to IC analysis. The retention times of the peaks corresponding to the predicted components in each peak of the measurement sample are compared with the retention times of the known samples, and if they match, the prediction is presumed to be correct. (Quantitative analysis) Quantitative analysis is performed using the calibration curve method. First, a known sample of the predicted component with a known concentration is measured, and a calibration curve is created. The calibration curve is calculated using the coefficient of determination (r 2 ) is between 0.999 and 1. The amount of the predicted component in the measurement sample is calculated from the calibration curve and the area of the peak of the predicted component in the measurement sample. The above process is carried out for all peaks detected in the IC analysis of the measurement sample, and the amount of each predicted component is calculated.
[0055] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.
[0056] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, EC is preferred.
[0057] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, EMC is preferable.
[0058] As the non-aqueous solvent, it is preferable to use a cyclic carbonate or a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When a cyclic carbonate and a chain carbonate are used in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.
[0059] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.
[0060] The lithium salt is LiPF 6 , LiPO 2 F 2 , LiBF 4 , LiClO 4inorganic lithium salts such as lithium oxalate (LiBOB), lithium difluorooxalate (LiFOB), lithium bis(oxalate) difluorophosphate (LiFOP), and other lithium oxalates; LiSO 3 CF 3 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ), LiC(SO 2 CF 3 ) 3 , LiC(SO 2 C 2 F 5 ) 3 Among these, inorganic lithium salts are preferred, and LiPF 6 is more preferred.
[0061] The content of electrolyte salt in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the non-aqueous electrolyte can be increased.
[0062] The nonaqueous electrolyte of the nonaqueous electrolyte storage element contains an imide salt. The imide salt is lithium (difluorophosphonyl)fluorosulfonylimide, lithium bis(fluorosulfonyl)imide, lithium bis(difluorophosphonyl)imide, or a combination thereof. By containing the imide salt in the nonaqueous electrolyte, the BET specific surface area is increased to 6.0 m. 2 When a negative electrode active material having a capacitance of 1000 .mu.m or less is used, the nonaqueous electrolyte electricity storage element is highly effective in reducing the occurrence of continuous irreversible capacity in the negative electrode.
[0063] As the imide salt, from the viewpoint of further reducing the occurrence of continuous irreversible capacity in the negative electrode, lithium (difluorophosphonyl) fluorosulfonylimide and lithium bis(difluorophosphonyl)imide are preferred, and lithium (difluorophosphonyl) fluorosulfonylimide is more preferred.
[0064] The lower limit of the content of the imide salt in the non-aqueous electrolyte is preferably 0.2% by mass, more preferably 0.5% by mass. Meanwhile, the upper limit of the content of the imide salt is preferably 2.5% by mass, more preferably 2.0% by mass. When the content of the imide salt in the non-aqueous electrolyte is within the above range, the effect of suppressing the reductive decomposition of the imide salt in the negative electrode can be improved. In particular, when the content of the imide salt is equal to or less than the above upper limit, the reductive decomposition of the imide salt present in excess can be prevented. Therefore, the continuous generation of irreversible capacity in the negative electrode of the non-aqueous electrolyte storage element can be more effectively reduced.
[0065] The non-aqueous electrolyte preferably further contains an oxalate complex salt. The oxalate complex salt refers to a salt containing a complex ion having an oxalate ligand. By the non-aqueous electrolyte further containing an oxalate complex salt, reductive decomposition of the non-aqueous electrolyte in the negative electrode can be further suppressed.
[0066] Examples of oxalate complex salts include lithium bis(oxalate)borate (LIBOB), lithium difluorooxalateborate (LIFOB), and lithium tetrafluorooxalatephosphate (LIPF 4 (Ox)) and lithium difluorobisoxalate phosphate. From the viewpoint of protecting the negative electrode and suppressing gas generation, the oxalate complex salt preferably contains a boron atom, such as LIBOB and LIFOB.
[0067] The lower limit of the content of the oxalate complex salt in the non-aqueous electrolyte is preferably 0.1% by mass, more preferably 0.2% by mass. Meanwhile, the upper limit of this content is preferably 1.0% by mass, more preferably 0.5% by mass. When the content of the oxalate complex salt is within the above range, the protective effect of the negative electrode can be further improved. When multiple types of oxalate complex salts are contained, the content of the oxalate complex salt means the total mass of the multiple oxalate complex salts.
[0068] The non-aqueous electrolyte may contain other components other than the non-aqueous solvent, the electrolyte salt, the imide salt, and the optional oxalato complex salt, as long as the effects of the present invention are not impaired. Examples of the other components include various additives contained in the non-aqueous electrolyte of a general non-aqueous electrolyte storage element. However, the content of these other components in the non-aqueous electrolyte is preferably 5% by mass or less, more preferably 1% by mass or less.
[0069] The non-aqueous electrolyte can be obtained by dissolving any of the components, such as the electrolyte salt, the imide salt, and the oxalato complex salt, in the non-aqueous solvent.
[0070] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.
[0071] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the energy storage element.
[0072] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.
[0073] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.
[0074] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.
[0075] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.
[0076] <Configuration of the power storage device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in an automobile power source such as an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc., a power source for electronic devices such as a personal computer and a communication terminal, or a power storage power source, etc. In this case, the technology of the present invention may be applied to at least one nonaqueous electrolyte storage element included in the electricity storage device.
[0077] 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of the one or more nonaqueous electrolyte electricity storage elements 1. <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The method for producing the nonaqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The method includes, for example, preparing an electrode body, preparing a nonaqueous electrolyte containing an imide salt, and housing the electrode body and the nonaqueous electrolyte in a container. The preparation of the electrode body includes preparing a positive electrode and a nonaqueous electrolyte having a BET specific surface area of 6.0 m 2 / g or less, and stacking or winding the positive electrode and the negative electrode with a separator interposed therebetween to form an electrode assembly.
[0078] The method of housing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution may be injected through an injection port formed in the container, and then the injection port may be sealed.
[0079] <Other embodiments> The nonaqueous electrolyte storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.
[0080] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (e.g., a lithium ion secondary battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors.
[0081] In the above embodiment, the electrode assembly in which the positive electrode and the negative electrode are stacked with a separator interposed therebetween has been described, but the electrode assembly may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. EXAMPLES
[0082] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0083] [Examples 1 to 3 and Comparative Examples 1 to 3] (Negative electrode) A negative electrode mixture paste was prepared containing a negative electrode active material made of graphite shown in Table 1, styrene-butadiene rubber (SBR) as a binder, and carboxyl methyl cellulose (CMC) as a thickener, with water as a dispersion medium. The ratio of the negative electrode active material, binder, and thickener was 98:1:1 in terms of mass ratio of solid content. This negative electrode mixture paste was applied to both sides of a strip-shaped copper foil as a negative electrode substrate, dried, and pressed to form a negative electrode active material layer, thereby obtaining negative electrodes of the examples and comparative examples. The BET specific surface area of the negative electrode active material is shown in Table 1.
[0084] (Non-aqueous electrolyte) A non-aqueous solvent was prepared by mixing EC, DMC, and EMC in a volume ratio of 30:35:35, and lithium hexafluorophosphate (LiPF 6 ) at 1.2 mol / dm 3Into this solution, lithium (difluorophosphonyl)fluorosulfonylimide, which is an imide salt, and lithium bis(oxalato)borate and vinylene carbonate, which are contained in the amounts shown in Table 1, were dissolved to obtain a non-aqueous electrolyte. In Table 1 below, "-" indicates that the corresponding component was not used.
[0085] (positive electrode) NCM111(LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 A positive electrode was prepared using the positive electrode active material as the positive electrode active material. The positive electrode contained the positive electrode active material, polyvinylidene fluoride (PVDF) as a binder, and acetylene black as a conductive agent, and a positive electrode mixture paste was prepared using N-methyl-2-pyrrolidone (NMP) as a dispersion medium. The ratio of the positive electrode active material, binder, and conductive agent was 93:4.5:2.5 in terms of mass ratio of solid content. This positive electrode mixture paste was applied to both sides of a strip-shaped aluminum foil as a positive electrode substrate, dried, and pressed to form a positive electrode active material layer, thereby obtaining a positive electrode.
[0086] (Preparation of non-aqueous electrolyte storage element) Next, the positive electrode and the negative electrode were laminated with a separator made of a polyethylene microporous film interposed therebetween to prepare an electrode assembly. The electrode assembly was placed in an aluminum rectangular container, and a positive electrode terminal and a negative electrode terminal were attached. The nonaqueous electrolyte was poured into the container, which was then sealed to obtain the nonaqueous electrolyte storage elements of the examples and comparative examples.
[0087] (Initial charge / discharge) The obtained non-aqueous electrolyte storage element before charging and discharging was subjected to two cycles of initial charging and discharging at 25°C in the following manner. In the first cycle, constant current and constant voltage charging was performed with a charging current of 0.2C, a charging cut-off voltage of 4.1V, and a total charging time of 7 hours, followed by a rest period of 10 minutes. Then, constant current discharging was performed with a discharging current of 0.2C and a discharging cut-off voltage of 2.75V, followed by a rest period of 10 minutes. In the second cycle, constant current and constant voltage charging was performed with a charging current of 1.0C, a charging cut-off voltage of 4.1V, and a total charging time of 3 hours, followed by a rest period of 10 minutes. Then, constant current discharging was performed with a discharging current of 1.0C and a discharging cut-off voltage of 2.75V, followed by a rest period of 10 minutes. The initial charging and discharging were performed by the above operations.
[0088] [evaluation] (Calculation of irreversible capacity in negative electrode) The difference between the charge capacity and the discharge capacity in the second cycle of the initial charge and discharge of each of the storage elements of Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 was calculated and used as the irreversible capacity. Here, since it can be considered that the irreversible capacity in the positive electrode hardly occurs in the second cycle of the initial charge and discharge, this irreversible capacity was used as the irreversible capacity in the negative electrode. Then, the ratio of the irreversible capacity in each of the negative electrodes of Example 1 to Example 3 to the irreversible capacity in the negative electrode of Comparative Example 1 and the ratio of the irreversible capacity in the negative electrode of Comparative Example 3 to the irreversible capacity in the negative electrode of Comparative Example 2 were calculated as the ratio [%] of the negative electrode irreversible capacity of the imide salt-added sample to the imide salt-free sample. The results are shown in Table 1.
[0089] [Table 1]
[0090] As shown in Table 1, the BET specific surface area of the negative electrode active material is 6.0 m 2 / g or less, and the non-aqueous electrolyte contains an imide salt. 2 / g or less, and as compared with Comparative Example 1 in which the non-aqueous electrolyte does not contain an imide salt, it can be seen that the inclusion of an imide salt in the non-aqueous electrolyte has a high effect of reducing the occurrence of continuous irreversible capacity in the negative electrode. 2 / g and the non-aqueous electrolyte did not contain an imide salt. 2 / g, and from a comparison with Comparative Example 3 in which the non-aqueous electrolyte contains an imide salt, it can be seen that even if the non-aqueous electrolyte contains an imide salt, the BET specific surface area of the negative electrode active material is 6.0 m 2 It can be seen that when the amount of the electrolyte exceeds 100% by weight / g, the effect of reducing the occurrence of continuous irreversible capacity in the negative electrode decreases.
[0091] As described above, it was demonstrated that the nonaqueous electrolyte electricity storage element is highly effective in reducing the occurrence of continuous irreversible capacity in the negative electrode. [Industrial Applicability]
[0092] The present invention is suitably used as a nonaqueous electrolyte storage element, including a nonaqueous electrolyte secondary battery, which is used as a power source for electronic devices such as personal computers and communication terminals, automobiles, and the like. [Explanation of symbols]
[0093] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device
Claims
1. a negative electrode including a negative electrode active material; a positive electrode including a positive electrode active material; A non-aqueous electrolyte containing an imide salt; It is equipped with The BET specific surface area of the negative electrode active material is 6.0 m 2 / g or less, The nonaqueous electrolyte electricity storage element, wherein the imide salt is lithium (difluorophosphonyl)fluorosulfonylimide, lithium bis(fluorosulfonyl)imide, lithium bis(difluorophosphonyl)imide or a combination thereof.
2. 2. The nonaqueous electrolyte storage element according to claim 1, wherein the content of the imide salt in the nonaqueous electrolyte is from 0.5% by mass to 2.0% by mass.
3. The potential of the positive electrode at the end of charge voltage during normal use is 3.9 V (vs. Li / Li + 3. The nonaqueous electrolyte storage element according to claim 1, wherein the content of the nonaqueous electrolyte is equal to or greater than 1.
Citation Information
Patent Citations
Negative pole material for lithium battery, and lithium battery
JP2005222933A